2016
DOI: 10.18632/oncotarget.7157
|View full text |Cite
|
Sign up to set email alerts
|

NOTUM is a potential pharmacodynamic biomarker of Wnt pathway inhibition

Abstract: Activation of Wnt signaling due to Wnt overexpression or mutations of Wnt pathway components is associated with various cancers. Blocking Wnt secretion by inhibiting PORCN enzymatic activity has shown efficacy in a subset of cancers with elevated Wnt signaling. Predicting response to upstream Wnt inhibitors and monitoring response to therapeutics is challenging due to the paucity of well-defined biomarkers. In this study we identify Notum as a potential biomarker for Wnt driven cancers and show that coordinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…CFPAC-1 has no known mutation in Wnt pathway but is sensitive to β-catenin knockdown ( Supplementary Fig. S1), as well as PORCN inhibitor [35]. EGI-1, a cholangiocarcinoma cell line with a RSPO3 translocation that confers Wnt dependency, was also included in the drug combination study ( Supplementary Fig.…”
Section: A Drug Combination Study Reveals the Synergy Between Porcn Imentioning
confidence: 99%
“…CFPAC-1 has no known mutation in Wnt pathway but is sensitive to β-catenin knockdown ( Supplementary Fig. S1), as well as PORCN inhibitor [35]. EGI-1, a cholangiocarcinoma cell line with a RSPO3 translocation that confers Wnt dependency, was also included in the drug combination study ( Supplementary Fig.…”
Section: A Drug Combination Study Reveals the Synergy Between Porcn Imentioning
confidence: 99%
“…Recent data show that cleavage of the essential palmitoleate moiety by the carboxylesterase Notum is an important regulatory process to reduce Wnt signalling range [ 25 ]. Extracellular levels of Notum in the blood serves as a biomarker for Wnt-driven cancer [ 26 ]. In the case of glycosylation, the number of glycosylation residues varies between the different Wnts and it is possible this modification is dispensable for its activity [ 27 , 28 ].…”
Section: Hh and Wnt Molecules Are Both Lipid-modified And Strongly Asmentioning
confidence: 99%
“…Earlier studies have shown that NOTUM regulates development in Drosophila, while its function in mammals was only recently characterized (25). NOTUM is overexpressed in hepatocellular carcinoma (28) and is also related to gastric cancer (34). These observations suggest that NOTUM has a role in other cancer types but do not provide any association between NOTUM and CRC.…”
Section: Discussionmentioning
confidence: 94%